Mussel‐Inspired Biocoating for Improving the Adhesion of Dental Pulp Stem Cells in Dental Pulp Regeneration. Issue 24 (2nd June 2020) - Liu, Yanan; Qiu, Ying; Ni, Shilei; Zhang, Xuewei; Sun, Hongchen; Song, Wenlong; Li, Xiangwei
Abstract: Dental pulp engineering possesses a promising perspective to replacing lost pulp in the root canal and restoring its functions. Stable adhesion of dental pulp stem cells (DPSCs) on the root canal dentin wall is a key element required for reconstruction of a functional odontoblast layer in dental pulp regeneration. To address this challenge, dopamine‐modified hyaluronic acid (DA‐HA) is coated on dentin to obtain a stable adhesion of DPSCs. The dopamine segment provides adhesion ability to the coating, and the hyaluronic acid increases the biocompatibility. The results show that DPSCs can adhere on the DA‐HA coated dentin slice better than those without coating. Simultaneously, DPSCs proliferation can be further promoted on the prepared coating. Therefore, the DA‐HA coating may provide a possible way to immobilize odontoblast cell onto dentin surface for pulp regeneration. Abstract : Mussel‐inspired functional hyaluronic acid coating constructs stable adhesion between dental pulp stem cells and dentin, demonstrating a feasible therapeutic strategy for recovering the biological functions of diseased or damaged teeth that lost pulp tissue.